Mental Health and Well-Being during the First vs. Second COVID-19 Pandemic Lockdown in Cyprus - Papageorgiou, Danae; Kassianos, Angelos P.; Constantinou, Marios; Lamnisos, Demetris; Nicolaou, Christiana; Papacostas, Savvas S.; Gloster, Andrew T.; Karekla, Maria (My University, 2021)
Introduction: Following the onset of the COVID-19 pandemic, most countries imposed strict governmental lockdowns. Research investigating the psychological impact of pandemic-induced lockdowns is accumulating, though to date no study has examined the psychological health and associated parameters of well-being in countries that underwent additional lockdowns as the pandemic continued into resurgence "waves." Aim: The present study provides an overview of the psychological impact of COVID-19 across the two lockdowns in the Cypriot population. Methods: In total, 957 participants completed an online survey during the first lockdown, 134 of whom completed a similar survey again during the second lockdown. The outcomes assessed included stress, positive and negative affect, and well-being. Results: The results indicated no population-wide severe reactions in the participants. Repeated measures analyses showed similar mental health levels during both the first and the second lockdowns. Further inspection of participants scores indicated that, for all mental health variables, approximately half of the participants improved, while the other half deteriorated. Discussion: Perceived social support and psychological flexibility predicted most psychological outcomes during both lockdowns. Further research is necessary to understand the continuing effects of the pandemic and associated lockdowns on mental health.
Keywords: COVID-19; Pandemic; Psychological health; Protective factors; Lockdowns